The peregrine muse: studies in comparative Renaissance literature - Clements, Robert J. (Robert John), 1912-1993 (Studies in the Romance languages and literatures, 1959)
These essays illustrate how the muse of Italian Renaissance literature wandered throughout Western Europe, inspiring the best of writers: Ronsard, Lopez Pinciano, Burton, Marheurite de Navarre, Desportes, and indeed, even up until those as modern as Rilke.